Biometric Attendance Techniques in COVID-19: A Review: Hafiz Burhan Ul Haq, Akifa Abbas, Muhammad Amjad Khan, Memoona, Sabreena Nawaz - Hafiz Burhan Ul Haq; Akifa Abbas; Muhammad Amjad Khan; Memoona; Sabreena Nawaz (International Journal for Electronic Crime Investigation, 2021)
Nowadays COVID-19 is spreading everywhere which has badly affected the countries from social as well as economical perspectives. According to SOP people have to maintain social distancing, use a face mask and avoid biometric devices for attendance in order to prevent the coronavirus. Several techniques have been developed in order to maintain the attendance in Covid-19 pandemic by considering the precautions to reduce the spread of coronavirus. This paper provides a review of the biometric techniques such as face recognition, palm recognition, face mask detection, face recognition, and iris detection techniques adopted in COVID-19 to maintain/mark attendance in organizations/institutes. However, the challenges of the Covid-19 techniques also are part of this paper that highlights the issues in current techniques. The prime focus of this study is to differentiate biometric methods for researchers or users to decide which tools are better for their requirements.